Undoing citizenship. Undocumented queer activism and practices of rights. - Pieri, Mara (2016)
Within the emergence of migrant activism, the experience of UndocuQueers developed in San Francisco from 2011 challenges common assumption about practices in migrant movements through the intersections between queer and migrant claims. In order to understand their peculiarities, I will first analyse some of the salient characters of UndocuQueer activism. Then, I will focus on the web-series “Undocumented and awkward”, in order to discuss the intersectionalities proposed by the movement. In the third part, I will discuss how the series may be framed as examples of groundbreaking practices of citizenship. I will finally argue that UndocuQueer movement and its cultural production offer a ground-breaking example of political practices of rights and propose a promising perspective for a critical engagement with citizenship issues.